PENEGAKAN TINDAK PIDANA CYBERSTALKING DALAM HUKUM POSITIF INDONESIA - Pratama, Akbar Yudha; Br, Hafidz Amrullah Dzaky Nugroho; Astinda, Afifudin Nur Rosyid; Adhipradana, Yurista Ardien (Legal Standing : Jurnal Ilmu Hukum, 2024)
Improper use of social media often leads someone to deal with the law. Many social media users are not aware of the legal consequences of wrong treatment, for example, speaking rudely, disturbing someone, harassing someone, cyberstalking, cyberbullying, and so on. The public only realizes the mistake when the victim brings the problem to law enforcement. The purpose of this study is to explain how to enforce cyberstalking crimes from a positive legal perspective. This study is a normative legal study with a statutory approach. In the implementation of regulations in Indonesia through the Electronic Information and Transactions Law (ITE) on many legal problems that occur on social media, it often makes the perpetrators surprised and regret their actions on social media. In addition, preventive measures are also very important in reducing the risk of cyberstalking.